Introduction: Multimodal Anthropology and the Politics of Invention - Dattatreyan, Ethiraj Gabriel; Marrero‐Guillamón, Isaac (American anthropologist, 2019)
This introduction and the articles included in this special series (spread across several issues of this journal) theorize the possibilities--and pitfalls--that emerge as anthropologists utilize a combination of audio, video, text, still images, performance methodologies, and web platforms to iteratively, collaboratively, and sensually generate relations with research participants, interdisciplinary colleagues, and others. We are not necessarily interested in developing multimedia approaches to representing or disseminating anthropological knowledge; rather, we are concerned with how multimodality may contribute to a politics of invention for the discipline.